Study on Energy Consumption Assessment Method and Model of FTTH Network - Zhanhai Zhuang; Yan Jiang (Dianxin kexue)
FTTH has become the main solution of the last mile access network construction. As the development of FTTH network, the energy consumption of the access network must be focus on. But now the effective means of energy consumption assessment for FTTH network is lack. According to research and analysis of the energy consumption influencing factors, this paper builds a FTTH network energy consumption model. It can realize visualization and assessment of FTTH network energy consumption, and provide recommendation and reference for operators to achieve saving energy and emission reduction.